Kp والمعامل الجيومغناطيسي F10.7 حساب تغيرات كثافة الغلاف الجوي العلوي من خلال تأثرها بمعاملات النشاط الشمسي معامل الفيض الراديوي الشمسي - مزهر عبيدرواء (University of Thi-Qar Journal of Science, 2019)
The atmospheric density variations is studied under the effect of solar activity at altitude of low orbital satellites, the atmospheric density is determined from through its influence by the solar activity parameters (The radio solar flux parameter (F10.7) and geomagnetic activity parameter (Kp)).This study based on Total Density(TD88 )model for calculating this variations. The results show that, the determined upper atmospheric density is changing according to change the solar activity parameters, diurnal and annual variations.